Soybean (Glycine max) oil bodies and their associated phytochemicals - Fisk, Ian D.; Gray, David A. (Wiley, 2011)
Abstract:  Soybean oil bodies were isolated from 3 cultivars (Ustie, K98, and Elena) and the occurrence of 2 classes of phytochemicals (tocopherol isoforms and isoflavones) and strength of their association with isolated oil bodies was evaluated. Tocopherol is shown to be closely associated with soybean oil bodies; δ-tocopherol demonstrated a significantly greater association with oil bodies over other tocopherol isoforms. Isoflavones do not show a significant physical association with oil bodies, although there is some indication of a passive association of the more hydrophobic aglycones during oil body isolation.